Comparison of outcome between suture and suture-less surgery following pterygium excision and conjunctival autograft - Chandra Shekhar Majumder; M. Shafiqul Alam; Hosne Ara; Robiul Islam; Sheikh Mohammad Rashedul Haque (International Journal of Research in Medical Sciences, 2023)
Background: A pterygium, known as surfer's eye, is a raised, wedge-shaped growth of the conjunctiva that extends onto the cornea, the outer layer of the eye. Aim was to compare the safety, efficacy and outcome of suture less technique with suture of conjunctival autograft in the management of pterygium. Methods: This study was carried out in the department of ophthalmology, Sir Salimullah medical college and Mitford hospital, Dhaka. Study period was July 2019 to June 2020. Subjects for this study were divided into two groups, forty patients were enrolled in each group of the study population. Group I (control) comprised the subjects in whom suture was used following pterygium excision and conjunctival autograft and group II (experimental) comprised the subjects in whom no suture was used following pterygium excision and conjunctival autograft. Results: In group I, 20% were 20-29 years old, 30% were 30-39, 27.5% were 40-49, and 22.5% were over 50, with 77.5% being male and 22.5% female. In group II, 22.5% were 20-29 years old, 27.5% were 30-39, 30% were 40-49, and 20% were over 50, with 72.5% being male and 27.5% female. The most common symptom was "foreign body sensation" in both groups. In group I, 5% experienced partial graft dehiscence, 2.5% a conjunctival cyst, 10% hyperemia, and 17.5% visual improvement. In group II, 2.5% had partial graft dehiscence, 2.5% hyperemia, and 22.5% visual improvement. Neither group had graft retraction or recurrence. Conclusions: Postoperative presentation like hyperemia was significantly less in experimental group. Incidence of post-operative complications like graft dehiscence and conjunctival cyst were comparatively less frequent in suture less technique. Thus, suture less technique following pterygium excision and conjunctival autograft is a safer and less complicated than sutured technique.